Empowerment of PKBM Tutors Thru Training in Creating Digital Learning Media with Articulate Storyline - Citra Dwi Palenti; Pani Aswin; Ririn Gusti; Alfin Julianto (Universitas Negeri Padang, 2026)
The use of interactive, multimedia, and online learning media is becoming increasingly important to enhance the effectiveness of learning, in line with 21st-century skills that emphasize the improvement of technological abilities. An innovative learning process makes the learning process effective. PKBM tutors were trained to create digital media using Articulate Storyline. The training results show that Articulate Storyline overall successfully improved participants' understanding and skills, as evidenced by the number of participants who mastered the material in every aspect of the evaluation. Mastery of application usage was achieved with 65% understanding and 30% very understanding, while the ability to create teaching materials reached 75% mastery.